AKTIVITAS OLAHRAGA SISWA SEKOLAH MENENGAH ATAS - Hanif Badri (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
Based on the observations that conducted by the researcher in the field earlier showed that the active daily motion activities of students Senior High School state 10 Padang was very less and was expected to effect the achievement of their health and physical fitness negatively. The purpose of this study was to assess the sports activities of the students of senior High School state 10 Padang. The research used quantitative approach and designed descriptively. Numbers of the population were 854 students which were consist of boy and girl Student Senior High School State 10 Padang. The Sample was taken by Stratified Random Sampling Technique which totally are 129 students. Data was collected by questionnaire, observation and interviews, and analyzed with descriptive techniques. The results of the analysis of student sports activities of the Senior High School State 10 Padang showed that (1) most of students were very participate in sport activities in physical Education learning, (2) most of the students were participate in extracurricular learning, (3)most of the student were participate in exercise activities outside the school structurally, (4) most of the students were participate moderately in sports activities outside the school are unstructured, (5) most of the students had very high active in to sport activities and most of them felt the benefits of Exercise activities. Keywords : Students 'Sport Activities